Analysis of the Role of SMEs in Indonesia's Economic Growth in 2009-2018 - Winda Fitriatus Soleha Winda (Perkumpulan Praktisi Akuntansi Indonesia, 2022)
SMEs are considered to have an important role in encouraging the accelerated increase in per capita income and the improvement of the economy of a region. SMEs players are required to develop the economy of a country and compete between countries, so that they are able to advance the Indonesian economy. The data used in this research are secondary data from the Central Bureau of Statistics, the Ministry of Cooperatives and SMEs and literature studies related to this research. The dependent variable in this study is Indonesia's Gross Domestic Product (GDP), the independent variable used is the variable total of SMEs, the total of labor SME, investment and exports. This research uses multiple linear regression method. The purpose of this study was to analyze the effect of the total of SMEs, the effect of the total of labor SME, the effect of investment and the influence of exports from the SME sector on Indonesia's GDP. From the research results, it is known that the variables of the total of SMEs, investment and exports have no effect on GDP. It is different from the total of SME labor variable which significantly affects GDP. Overall the SME sector can affect Indonesia's economic growth.